2019
DOI: 10.1093/ejcts/ezz332
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of chest ultrasound for postoperative pneumothorax in comparison to chest X-ray after lung resecting surgery

Abstract: OBJECTIVES Thoracic ultrasound is superior to chest X-ray for the detection of a pneumothorax in trauma and intensive care medicine. Data regarding its use in non-cardiac thoracic surgery are scarce and contradictory. Previous studies are heterogeneous regarding sonographic methodology and patient selection. This study aimed to evaluate the accuracy of thoracic ultrasound for pneumothorax assessment after lung resecting surgery in unselected patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(53 citation statements)
references
References 20 publications
0
53
0
Order By: Relevance
“…The role of lung ultrasound as an alternative to routine chest roentgenograms for the detection of a pneumothorax after thoracic surgery is under discussion. Two large studies, which were performed under routine [ 16 ] or near-routine conditions [ 23 ], exhibited a low sensitivity (0.32, 0.19, respectively), whereas two smaller studies with rather artificial conditions (restrictive inclusion criteria [ 24 ], small sample size with very high pneumothorax rate [ 21 ]) revealed a 1.0 sensitivity. The reasons for this discrepancy are not clear; different sonographic examination techniques and inclusion criteria are suspected to be the cause.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The role of lung ultrasound as an alternative to routine chest roentgenograms for the detection of a pneumothorax after thoracic surgery is under discussion. Two large studies, which were performed under routine [ 16 ] or near-routine conditions [ 23 ], exhibited a low sensitivity (0.32, 0.19, respectively), whereas two smaller studies with rather artificial conditions (restrictive inclusion criteria [ 24 ], small sample size with very high pneumothorax rate [ 21 ]) revealed a 1.0 sensitivity. The reasons for this discrepancy are not clear; different sonographic examination techniques and inclusion criteria are suspected to be the cause.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a pneumothorax on the first day after surgery will be larger than later, otherwise one would not have decided to remove the chest tube. We have demonstrated that the sensitivity of ultrasound is dependent on the pneumothorax size [ 16 ]. Third, the examiner who – consciously or not – perceives an air leakage through a chest tube will probably expect a pneumothorax and examine more accurately (examiner bias / diagnostic suspicion bias [ 30 , 31 ]).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations